Higher antibody responses after mRNA-based vaccine compared to inactivated vaccine against SARS-CoV-2 in Behcet’s syndrome - Ozdede, Ayse; Nohut, Okan Kadir; Atli, Zeynep; Tok, Yeşim Tuyji; Guner, Sabriye; Yilmaz, Erkan; Ucar, Didar; Uygunoglu, Ugur; Hamuryudan, Vedat; Seyahi, Emire (Rheumatology international, 2022)
There are limited data about humoral response to vaccine in Behçet’s syndrome (BS). We compared SARS-CoV-2 antibody response after two doses of inactivated (Sinovac/CoronaVac) or mRNA (Pfizer/BioNTech) vaccines in patients with BS and healthy controls (HCs). We studied 166 (92M/74F) patients with BS (mean age: 42.9 ± 9.6 years) and 165 (75M/90F) healthy controls (mean age: 42.4 ± 10.4 years), in a single-center cross-sectional design between April 2021 and October 2021. A total of 80 patients with BS and 89 HCs received two doses of CoronaVac, while 86 patients with BS and 76 HCs were vaccinated with BioNTech. All study subjects had a negative history for COVID-19. Serum samples were collected at least 21 days after the second dose of the vaccine. Anti-spike IgG antibody titers were measured quantitatively using a commercially available immunoassay method. We found that the great majority in both patient and HC groups had detectable antibodies after either CoronaVac (96.3% vs 100%) or BioNTech (98.8% vs 100%). Among those vaccinated with CoronaVac, BS patients had significantly lower median (IQR) titers compared to HCs [36.5 (12.5–128.5) vs 102 (59–180), p < 0.001]. On the other hand, antibody titers did not differ among patients with BS and HCs who were vaccinated with BioNTech [1648.5 (527.0–3693.8) vs 1516.0 (836.3–2599.5), p = 0.512). Among different treatment regimen subgroups in both vaccine groups, those who were using anti-TNF-based treatment had the lowest antibody titers. However, the difference was statistically significant only among those vaccinated with CoronaVac. Among patients vaccinated with BioNTech, there was no statistically significant difference between different treatment regimen groups. Compared to inactivated COVID-19 vaccine, mRNA-based vaccine elicited higher antibody titers among BS patients. Only in the CoronaVac group, patients especially those using anti-TNF agents were found to have low titers compared to healthy subjects. BS patients vaccinated with BioNTech were found to have similar seroconversion rates and antibody levels compared to healthy controls. Further studies should assess whether the low antibody titers are associated with diminished protection against COVID-19 in both vaccine groups.